More food for thought: a follow-up qualitative study on experiences of food bank access and food insecurity in Ottawa, Canada - Anita Rizvi; Aganeta Enns; Lucas Gergyek; Elizabeth Kristjansson (BMC, 2022)
Abstract Background Despite the widespread proliferation of food banks in high-income countries over the past several decades, there is a paucity of data regarding the long-term experiences of the people who rely on food banks. We were unable to find any other studies with follow-up interviews later than 6 months after baseline. Objective This study examined the changes in the lived experiences of people who accessed food banks over a period of 18 months. Methods Semi-structured interviews were conducted with 11 people who accessed food banks in Ottawa, Canada and who had participated in a 6-month study that ended one full year before this follow-up study was done. Transcripts of the interviews were analyzed through a general inductive approach involving repeated readings and coding of relevant segments of text with NVivo software according to themes that emerged iteratively. Code reports were then used to discuss and reach consensus on a final set of themes. Results Three main themes emerged: (1) chronic physical and mental health issues intersecting with food bank access; (2) psychosocial impact of relying on food banks; and (3) living on a low income and dealing with poverty. Chronic physical and mental health conditions were prevalent among the participants. As well, 10 of the 11 participants in this 18-month follow-up continued to rely on food banks as a regular resource - not as an emergency relief measure - to supplement their nutritional needs. While most of the participants reported that food banks helped them in some way, many shortcomings were also noted regarding food amounts, quality and choice. Overall, there was little change reported since the 6-month follow-up. Conclusions The shortcomings reported by participants can mostly be attributed to the dependence of food banks on charitable donations; thus, despite the commendable work of food bank staff and volunteers, participants described the food assistance as inadequate. Additionally, long-term food bank usage was a common denominator in the lived experiences of all our participants; therefore, our findings reinforce the need for assistance programs that target long-term food insecurity and its underlying causes, to replace or supplement charity-based food bank programs.